On the determination of safety factors for machines using finite element computations - Getsov, Leonid (Materiali in tehnologije, 2008)
Principles for the selection of modern methods for the determination of local strength safety factors in design computations of GTE parts for static and cyclic loading are suggested. It is shown that the selection of methods for the evaluation of local strength safety factors should be carried out applying special criteria and computations including adequate models of visco-elasto-plasticity. On the basis of the analysis of computational practice the minimum values of local strength safety factors for static and cyclic loading, which may be recommended for FEM computations, have been proposed.
Keywords: preiskava materialov; trdnost; varnost; security; metode; finite element method; metoda končnih elementov; lezenje; obremenitev